2018
DOI: 10.4236/pp.2018.911036
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy for Restoring the HPG Axis in Pain Patients Treated with Long-Term Opioid Analgesics

Abstract: Opioids are a treatment option for a variety of chronic pain conditions. But long-term opioid use can be associated with side effects, including hypogonadism. Opioid-induced hypogonadism (OIhG) is associated with the alteration of the hypothalamic-pituitary-gonadal axis (HPG). In males, hypogonadism can result in erectile dysfunction, reduced libido, fatigue, worsening mood, and increased risk of osteoporosis; in females, it can result in changes in the menstrual cycle and reduced libido, among other effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Although secondary sexual problems due to buprenorphine treatment have not been well-studied, in a previous study of patients on opioid use disorder treated with buprenorphine, it was reported at least one sexual dysfunction in the 83% of the subjects [ 56 ]. Finally, the testosterone replacement therapy could be interesting for those patients with sexual dysfunction [ 57 ], although there are described important side effects [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although secondary sexual problems due to buprenorphine treatment have not been well-studied, in a previous study of patients on opioid use disorder treated with buprenorphine, it was reported at least one sexual dysfunction in the 83% of the subjects [ 56 ]. Finally, the testosterone replacement therapy could be interesting for those patients with sexual dysfunction [ 57 ], although there are described important side effects [ 58 ].…”
Section: Discussionmentioning
confidence: 99%